ARRANGEMENT OF THE CAMPUS AREA OF PANCA BUDI DEVELOPMENT UNIVERSITY IN FLOOD PREVENTION IN THE RAINY SEASON - Dian Syahputra; Abdi Sugiarto (Journal of Information Technology, computer science and Electrical Engineering, 2025)
The arrangement of the Panca Budi Development University (UNPAB) Campus area in preventing flooding in the rainy season is an important issue that must be considered to maintain the smooth running of lecture activities and the comfort of the campus environment. This study aims to analyze and design flood mitigation solutions by applying the concept of Integrated Water System Management (IWSM) which can effectively manage rainwater flow. IWSM is a holistic approach that integrates green infrastructure and technology to manage stormwater, reduce runoff, and improve water quality. The method used in this study is a qualitative approach with a descriptive analysis of the existing conditions of the campus and the potential for the application of IWSM. The results of the study show that the implementation of IWSM on the UNPAB campus can reduce flood risk by improving the drainage system, increasing green open space, and utilizing rainwater harvesting technology. In addition, these solutions also contribute to groundwater management and create a greener and more sustainable environment. This study recommends regular maintenance of water infrastructure and increased awareness and participation of the academic community in maintaining the sustainability of the IWSM system on campus.